2018
DOI: 10.31248/jasp2018.088
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of pitfall traps and hand-picking techniques for studying macroathropods abundance in vegetable plots and the influence of abiotic factors on their abundance in Jos, Nigeria

Abstract: Soil macroarthropods are important components that sustain the health and quality of agro-ecosystems for improved agricultural productions though are influenced by abiotic components of the environment. Macroarthropod collections vary across traps due to the fact that some traps can stand for a long time while others such as handpicking cannot. However, traps may be used as a rapid assessment tool to generate checklists for macroarthropod species present in an area within a very short time. To this end, a stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 27 publications
(30 reference statements)
1
5
0
Order By: Relevance
“…Chilopoda had the lowest level of dominance, as indicated by its total density accounting for only 0.26%. This finding aligns with the observations made by Ramzy (2015) in Assiut Governorate and Ishaya et al, (2019) in Nigeria. In the realm of Chilopoda, the species Lithobius sp.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Chilopoda had the lowest level of dominance, as indicated by its total density accounting for only 0.26%. This finding aligns with the observations made by Ramzy (2015) in Assiut Governorate and Ishaya et al, (2019) in Nigeria. In the realm of Chilopoda, the species Lithobius sp.…”
Section: Discussionsupporting
confidence: 93%
“…Ombugadu et al, (2017) demonstrated that catches by pitfall traps may be influenced by timing and placement of the traps. Ishaya et al, (2018) stated that the high variation between a pitfall and hand-picking techniques in favour of pitfall may probably be connected with the time the traps were left to stand. It may also be due to that the trap works throughout the time it stands, the number of catches may exceed that of the handpicking or it may possibly be that some of the soil macroarthropods are more active at night when it is difficult for them to detect the traps.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations